Pathogenetic role of omentin in the development of chronic diabetic complications - Soloviuk, O. O.; Nazarenko, O. V.; Soloviuk, O. A.; Солов'юк, Олександр Олегович; Назаренко, Олена Валеріївна (Barcelona : Barca Academy Publishing, 2024)
Aim: The objective is to ascertain the omentin-1 levels in obese individuals with T2DM and to evaluate the presence and character of the correlation between its levels and TIMS of the carotid arteries in these subjects.